THE SULFONATED CHITOSAN DERIVATIVES: SYNTHESIS AND THEIR APPLICATION FOR CURCUMIN DELIVERY - Herayati
Curcumin, a hydrophobic compound, is an active compound that has many therapeutic activities. However, the util i zation of curcumin as a supplement is very limitf•d because of its low water solubility a nd poor chemical stability. It stimu lates the developing of severa l encapsulation methods for the curcumin in ord er to improve its water solubilit y and chemical stability. Chitosan, a po l ymeric compound which has high natural abunda nce, is one of the potential candida tes as a m atrix polymer for curcumin beca use of its biodegradable, biocompa tibl e and low tox icity characteristics. However, chitosa n has low solubilit y in water. So that, i>1 thi s research, two chitosan deriva tives; N-anisimine-0-sulfate-chitosan and N benzylsulfonate-chitosan, were prepared. Their chemical structures were confirmed by FTIR and NMR.